Test the Optical and Structural Characteristics of Nano PbO Produced by Plasma–jet Technique - Omar A. Gadaan; Kadhim A. Aadim; K. H. Razyg (Tikrit Journal of Pure Science)
The induced plasma technique was used in the current investigation to create lead oxide nanoparticles from bulk structures at various bombardment periods (4,6,8,10) min. The process will be carried out in the presence of argon gas that flows at a constant rate (3 L/sec). These nanoparticles were created as thin layers on various thicknesses of glass substrates prepared at different times of shelling”. After that, they were analyzed with an x-ray spectrum, scanning electron microscope (SEM), atomic force microscope (AFM) and UV-visible spectrophotometer. Where the optical characteristics and constants were examined, the energy gap of the films varied with bombardment periods from  2.1 ~1.98eV. The SEM and AFM images clearly display a structure that varies with bombardment duration due to the fluctuation in the diameter of the nanoparticles. Finally, the layers' entire amorphous nature is revealed by the x-ray spectrum.